สภาพคล่องและอัตราผลตอบแทนของหุ้นสามัญ : การศึกษาจากตลาดหลักทรัพย์แห่งประเทศไทย - จิราลักษณ์ สุวรรณสิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This study investigates a relation between stock returns and liquidity as proxied by share turnover, trading volume and estimated bid-ask spread (Roll s model (1984)). Additionally, the study examines the sensitivity of liquidity to stock price movement, together with potential determinants of that sensitivity. Data used are based mainly on weekly data of common stocks registered with Stock Exchange of Thailand, from 1994 to 2001. I firstly investigate the relation between stock returns and liquidity and find that the relation between stock return and liquidity does exist. However, the way they relate to each other is not consistent, depending on which proxies for liquidity and which time periods are used. Using share turnover and trading volume as proxy for liquidity, stock return relates positively with liquidity in the years before 1999. This result conflicts with the hypothesis stating low-liquidity stocks would offer high returns to compensate for the low liquidity. However, in 1999-2002, stock return is negatively related to liquidity. When using bid-ask spread as proxy for liquidity, the relation between stock return and liquidity is significant in only 1 year. For the study of sensitivity of liquidity to stock price movement, I investigate the co-movement between liquidity and absolute stock return, as well as the sensitivity of liquidity to stock price movement. The results show that absolute stock return is an important determinant of liquidity. I then try to identify the cross-sectional determinants of this co-movement and find that firm size is the only significant determinant. Other factors, including share turnover, return volatility, and share turnover volatility, hardly influence that co-movement.